Impact of Individual Process Parameters on Extraction of Polysaccharides from Saccharina latissima - Khajavi Ahmadi, Elmira; Al-Hamimi, Said; Jönsson, Madeleine; Sardari, Roya R. R. (Marine Drugs, 2025)
While numerous extraction methods have been applied to the brown algae Saccharina latissima, a systematic evaluation of how individual extraction parameters influence the extraction of each target polysaccharide has not previously been reported. Accordingly, this study compared conventional and advanced techniques for extracting fucoidan, laminarin, and alginate from pre-treated biomass. Conventional methods employed diluted acid (0.01 M and 0.1 M HCl), diluted alkali (0.01 M and 0.1 M NaOH), and hot water (121 °C for 30/60 min) for extraction. Advanced techniques involved pressurized liquid extraction (PLE) using water and moderate electric field (MEF) extraction with conditions optimized by statistical experimental design. Pre-treatment with aqueous ethanol removed 30% ash and eliminated mannitol, improving extraction selectivity. The results demonstrated fucoidan yields of 31% with 0.01 M HCl and 46% with 0.1 M NaOH, while 0.01 M NaOH facilitated laminarin co-extraction (45%). Alginate, as a mannuronic acid polymer, was obtained at 9% yield with 0.1 M HCl, 42% yield with 0.1 M NaOH, and 27% with pressurized hot water for 30 min. High-temperature, short-duration PLE further improved alginate yield, while MEF showed limited gains due to high ionic content but demonstrated potential under optimized settings. The results support a cascading biorefinery approach in which different polysaccharide fractions can be sequentially obtained, contributing to more sustainable seaweed valorization.